Analysis of Indonesia’s National Cultural Image Representation on The Ministry of Foreign Affairs Official Website - Liza Yosephine Tambunan; Andi Faisal Bakti (CoverAge: Journal of Strategic Communication, 2016)
As the government institution that handles the international affairs of the nation, the Ministry of Foreign Affairs of the Republic of Indonesia holds the responsibility of representing Indonesia to its international counterparts. The official website of the Foreign Ministry, www.kemlu.go.id, is the hub of information provided by the institution with news stories submitted from domestic sources and also from Indonesia’s official diplomatic representative overseas. This research aims to analyze how Indonesia’s national cultural image is represented on the official website of the Ministry of Foreign Affairs RI, www.kemlu. go. id. Moreover, this research also aims to analyze the aspects of ‘representation and the real’, as well as analyzing how ‘positive and negative images’ are represented on the website. This research employs a qualitative approach in analyzing aspects of ‘representation and the real’ and ‘positive and negative images’ of Indonesia’s national cultural image representation on the website. Data collected are in the form of documentation of news stories published on the website. Research findings show that the Foreign Ministry illustrates representations that are in favor of Indonesia and protective of its national culture. The website presents key aspects of Indonesian culture that contribute to a positive representation.